Assessment of Adoption Gaps in Gobhi Sarson (Brassica Napus L.) Production Technologies in Amritsar and Tarntaran Districts of Punjab - S S Walia , Rajni , Satpal Singh , C S Aulakh; R S Gill (Indian Journal of Extension Education, 2013)
The present study was undertaken in Amritsar and Tarntaran districts of Punjab to analyze the status of gobhi sarson production technology, constraints in its cultivation and the possibilities of increasing production. Afundamental problem to overcome insignificantly increasing oilseed production is to change the prevailing perceptions of their status as a subsistence crop and to consider as a commercial crop. This will require aggressive on-farm demonstration of the viable technical options, to alleviate the gaps in technology of production of oilseed crops. It emphasizes dissemination of improved varieties and low-cost, environmental friendly crop husbandry techniques. Keeping this in view, front line demonstrations (FLDs) on gobhi sarson, existing technology v/s recommended technology were conducted during rabi 2010-11 and 2011-12 and have proved immensely useful in increasing the production and productivity of oilseed crops in the districts alongwith evaluation of adoption gaps. The improved practice produced 9.6 and 13.4 per cent more seed yield and 14.8 and 19.8 per cent higher net returns of gobhi sarson than the crop raised by farmers themselves in 2010-11 and 2011-12, respectively